2015
DOI: 10.1158/2326-6066.cir-14-0164
|View full text |Cite
|
Sign up to set email alerts
|

IFNγ Induces DNA Methylation–Silenced GPR109A Expression via pSTAT1/p300 and H3K18 Acetylation in Colon Cancer

Abstract: Short-chain fatty acids, metabolites produced by colonic microbiota from fermentation of dietary fiber, act as anti-inflammatory agents in the intestinal tract to suppress proinflammatory diseases. GPR109A is the receptor for short-chain fatty acids. The functions of GPR109A has been the subject of extensive studies, however, the molecular mechanisms underlying GPR109A expression is largely unknown. We show that GPR109A is highly expressed in normal human colon tissues, but is silenced in human colon carcinoma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 48 publications
2
38
0
1
Order By: Relevance
“…60 Loss of IFNg expression and function lead to increased cancer incidence including augmented colon carcinoma growth in vivo. 61 However, IFNg is also a master inducer of PD-L1 in human tumor cells. 58,59 The human CD274 gene promoter region has two IRF-binding consensus sequence elements and IFNg-activated IRF1 binds to these two DNA elements to upregulate PD-L1 expression in human tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…60 Loss of IFNg expression and function lead to increased cancer incidence including augmented colon carcinoma growth in vivo. 61 However, IFNg is also a master inducer of PD-L1 in human tumor cells. 58,59 The human CD274 gene promoter region has two IRF-binding consensus sequence elements and IFNg-activated IRF1 binds to these two DNA elements to upregulate PD-L1 expression in human tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our data determined that PD-L1 expression in MDSCs is also regulated by IFNg that activates pSTAT1 to directly regulate IRF1 transcription, and IRF1 directly binds to an unique IRF-binding consensus element to upregulate PD-L1 expression in MDSCs. Although IFNg is essential for host cancer immune surveillance against colon cancer development, 61 chronic IFNg signaling results in spontaneous colon cancer development. 63 It is possible that the chronic IFNg signaling might contribute to increased level of PD-L1 expression in MDSCs in the tumor microenvironment to promote colon cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin immunoprecipitation (ChIP) was performed using anti-H3K4me3 antibody and protein A agarose beads (Millipore, Temecula, CA) according to the manufacturer’s instructions as previously described (33). The immunoprecipitated genomic DNA was amplified by semi-quantitative PCR using four pairs of PCR primers (Table S1) covering the region from −3000 to +1000 relative to the nos2 transcription initiation site at the nos2 promoter region.…”
Section: Methodsmentioning
confidence: 99%
“…The Fas-mediated apoptosis pathway plays a key role in host cancer immune surveillance against spontaneous B lymphoma and colon carcinoma (22,32). In addition to H3K4me3, verticillin A also targets H3K9me3 to increase Fas expression in human colon cancer cells (30) …”
Section: Role Of Fasl In Suppression Of Pancreatic Tumor Growth In Vivomentioning
confidence: 99%
“…It has been reported that oncogenes such as AKT and STAT3 directly regulate constitutive PD-L1 expression in tumor cells (19,20). IFNc is a proinflammatory cytokine secreted by activated T and natural killer (NK) cells and acts as an essential component of the host cancer immune surveillance system (21,22). However, IFNc also acts as a master inducer of PD-L1 in tumor cells (16)(17)(18)23), suggesting that tumor cells may sense the elevated IFNc as a "threat" in the tumor microenvironment and adapt it by upregulating PD-L1.…”
mentioning
confidence: 99%